Analysis of Village Government Performance in Improving the Welfare of MSME Actors in Laut Dendang Village - Yuliana Pida; Sri Sudiarti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
MSMEs are the informal sector which contributes greatly to the nation's economy. And the village government is the government that is closest to the community and is directly related to MSME problems. So that the performance of the village government in dealing with MSMEs is an interesting topic to study. This study aims to identify and analyze the performance of the village government in improving the welfare of MSME actors in Laut Dendang Village. The analysis was carried out using qualitative methods. Data were obtained through exclusive interviews, direct field observations and documentation. Data analysis was done by triangulation method. The results of the study indicate that the performance of the village government as measured by using five indicators namely productivity, service quality, responsiveness, responsibility, and overall accountability has been carried out well. However, what needs to be emphasized is the productivity aspect which has not shown significant results but still shows positive developments.